Placing Nostalgia: Affect and Photography in the New Saskatchewan (Imaginations: Journal of Cross-Cultural Image Studies, 2016)
Abstract | The old social-democratic Saskatchewan has died. In its place, a neoliberal New Saskatchewan has taken hold over culture, politics, emotions, and the economy. This article situates the photography of Saskatchewan-based photographers Valerie Zink and Vera Saltzman within this shift to the oil-based neoliberal economies of the New Saskatchewan. I argue that Zink and Saltzman both work reparatively against the future-oriented place-making strategies of neoliberalism, constructing new affective economies through a critical engagement with nostalgia. Placed side by side, Zink’s and Saltzman’s photographs remind us of the place of Indigenous peoples and the importance of water to the flourishing of life. Their photographs develop an alternative affective economy in which the circulation of nostalgia as both a spatial and temporal affect unsticks optimism from neoliberalism, scrambles its neat teleologies, collapses regional distinctions, and accounts for the human and environmental cost of the New Saskatchewan’s unbridled optimism. By playing with and placing nostalgia, Zink and Saltzman invert the New Saskatchewan’s future-orientation, producing an alternative affective economy attentive to those left out of the New Saskatchewan.Résumé | L’ancienne Saskatchewan socio-démocrate est morte. A sa place une Saskatchewan néolibérale a pris en main la culture, la politiques les émotions et l’économie. Cet article met en contexte les œuvres des photographes saskatchewanaises Valerie Zink et Vera Saltzman au cœur de ce changement vers une économie néolibérale reposant sur l’industrie du pétrole dans cette nouvelle Saskatchewan. J’avance que Zink et Saltzman utilise une approche reparative dans leurs œuvres, contre les stratégies de construction d’espace tournées vers le futur du néolibéralisme et construisent de nouvelles économies affectives à travers un engagement critique avec le concept de nostalgie. Mises côte à côte, les images de Zink et Saltzman nous rappellent la place des peuples autochtones et l’importance de l’eau dans l’épanouissement de la vie. Leurs images développent une économie affective alternative dans laquelle la circulation de la nostalgie en tant qu’affect spatial et temporel ôte tout optimisme au néolibéralisme, chamboule ses téléologies bien nettes, détruit ses distinctions régionales et prend en considération les couts humains et environnementaux de l’optimisme sans limite de la nouvelle Saskatchewan. En mettant en contexte et en jouant avec la nostalgie, Zink et Saltzman renversent l’orientation vers le futur de la nouvelle Saskatchewan et produisent une économie affective alternative qui portent attention à ceux qui sont laissés de côté.